Pelatihan Pembuatan Pupuk Organik Cair Dari Limbah Bonggol Pisang: Upaya Sustainable Agriculture Di Desa Pisang Baru, Lampung - Jani Master; Arafi Iqhbal Islamy; Riza Andriantha; Adinda Choiriah; Syifa Salsabila R; Annisya Rianta Raudatuljannah; Yulia Nurainy; Erika Fitri Sari (CV. Multi Kreasi Media, 2024)
As an additional nutrient that can enhance plant fertility, fertilizer is a crucial factor in achieving plant productivity. One type of fertilizer that is good to use is organic fertilizer, which is derived from the fermentation or composting of plant and animal residues. Organic fertilizer can be made at home using household organic waste. In Pisang Baru Village, a considerable amount of banana stem waste is often discarded by the community. Based on this condition, this activity is aimed at providing training and understanding to the community of Pisang Baru Village regarding liquid organic fertilizer from banana stem waste. The activity is conducted through presentations, hands-on practice, and discussions with participants who are members of farmer groups. The results of this activity indicate that farmers who participated in the training show a high level of interest in using organic fertilizer on their agricultural land, which has the potential to realize sustainable agriculture through the use of organic fertilizers.